Systemic Antiangiogenic Therapies for Bleeding in Hereditary Hemorrhagic Telangiectasia: A Practical, Evidence-Based Guide for Clinicians - Al-Samkari, Hanny (Seminars in Thrombosis and Hemostasis, 2022)
Management of bleeding in hereditary hemorrhagic telangiectasia (HHT), the second most common hereditary bleeding disorder in the world, is currently undergoing a paradigm shift. Disease-modifying antiangiogenic therapies capable of achieving durable hemostasis via inducing telangiectasia regression have emerged as a highly effective and safe modality to treat epistaxis and gastrointestinal bleeding in HHT. While evidence to date is incomplete and additional studies are ongoing, patients presently in need are being treated with antiangiogenic agents off-label. Intravenous bevacizumab, oral pazopanib, and oral thalidomide are the three targeted primary angiogenesis inhibitors, with multiple studies describing both reassuring safety and impressive effectiveness in the treatment of moderate-to-severe HHT-associated bleeding. However, at present there is a paucity of guidance in the literature, including the published HHT guidelines, addressing the practical aspects of antiangiogenic therapy for HHT in clinical practice. This review article and practical evidence-based guide aims to fill this unaddressed need, synthesizing published data on the use of antiangiogenic agents in HHT, relevant data for their use outside of HHT, and expert guidance where evidence is lacking. After a brief review of principles of bleeding therapy in HHT, guidance on hematologic support with iron and blood products, and alternatives to antiangiogenic therapy, this article examines each of the aforementioned antiangiogenic agents in detail, including patient selection, initiation, monitoring, toxicity management, and discontinuation. With proper, educated use of antiangiogenic therapies in HHT, patients with even the most severe bleeding manifestations can achieve durable hemostasis with minimal side-effects, dramatically improving health-related quality of life and potentially altering the disease course.
Keywords: hereditary hemorrhagic telangiectasia; Osler–Weber–Rendu; treatment guidelines; bevacizumab; pazopanib; pomalidomide; thalidomide; angiogenesis; epistaxis; gastrointestinal bleeding